Revisiting the Past: Material Negotiations between the Classic Maya and an Entombed Sweat Bath at Xultun, Guatemala. Issue 1 (February 2021) - Clarke, Mary E.; Sharpe, Ashley E.; Hannigan, Elizabeth M.; Carden, Megan E.; Luna, Gabriella Velásquez; Beltrán, Boris; Hurst, Heather
Abstract : Large material accumulations from single events found in the archaeological record are frequently defined as evidence of ritual. They are interpreted as generalized deposit categories that imply rather than infer human motivations. While useful in the initial collection of data, these categories can, over time, become interpretations in and of themselves. The emic motivations behind the formation process of 'ritual deposits' ought to be considered using a relational ontology as an approach to understanding how past populations interacted with non-human actors, such as structures and natural features on the landscape. The present study evaluates the assembly and possible function of a dense deposit of artifacts recovered from a Classic period sweat bath at Xultun, Guatemala. Analyses of the various artifact types and human remains in the deposit in relation to what is known of the social history of the sweat bath itself illustrate ontological relationships among offered materials as well as between the offering and the personified place in which it was recovered. We observe that with a better understanding of place, it is possible to evaluate the ritual logic in Classic Maya material negotiations.